Modelling and characterisation of the IEEE 802.15.7 medium access control layer (MAC) for indoor Visible Light Communication (VLC) / Anuar Musa - Musa, Anuar (Institute of Graduate Studies, UiTM, 2017)
Radio Frequency (RF) technologies are presently the main medium for wireless communication systems. However, like many other technologies, RF has constraints such as limited bandwidth and electromagnetic interference which limit the applications of RF technologies in certain scenarios. For example, RF signals can cause interference with aircraft communication systems, medical equipment and devices in the hospital or navigational devices in airports. Meanwhile, current advancements in Light Emitting Diode (LED) devices and materials are driving the applications of Visible Light Communication (VLC). VLC combines both illumination and communication together within one device. VLC uses a white light LED as a source for the data transmission. Many opportunities exist to exploit the low-cost nature of LEDs and their lighting properties for widespread deployment of VLC. However, some characteristics of the optical wireless medium, including mobility, directionality, multi-user access and susceptibility to ambient light noise sources, must be managed and overcome. VLC system is standardised by IEEE 802.15.7 specification. In this dissertation, an analytical model and the ns-2 simulation model of the indoor Visible Light Communication (VLC) is developed and analysed based on the IEEE 802.15.7 standard. The analytical model is developed based on the Discrete Time Markov Chain (DTMC) method. The analytical model is compared with the theoretical CSMA model to verify the correctness of the proposed models.The throughput curves of the theoretical CSMA model, the DTMC analytical model, and the ns-2 simulation model follow the same pattern…